Aktualisasi Pendidikan Life Skill Untuk Meningkatkan Nilai-Nilai Spiritual Santri Di Pondok Pesantren Al-Qodiri Jember - Rizal, Syariful; Nardiyanto, Nardiyanto (Al-Riwayah : Jurnal Kependidikan, 2020)
This study discusses how the actualization of Life Skill Education to increase the Spiritual Values ​​of the Santri in Al-Qodiri Islamic Boarding School. Researchers use qualitative research methods. The results showed that Life Skill Education really provides and produces positive values ​​for pesantren because students are able to actualize their ability to achieve competence both as individuals and as part of the social community. High intellectual abilities are able to solve life problems faced in order to live an independent and dignified life and be proactive in solving existing problems. The management places the students in the area according to the ability of the students who are assisted by the regional management in exploring the potential of the students through activities in the region. Santri in the region emphasized that they can speak Arabic and read and write the book. Then the students followed the Ta'lim, Tahlilan and Dzikir Manaqib Syaich Abdul Qodir Jaelani. The spiritual values ​​that are emphasized for students are Social Values, Ethics, Morals and Cooperation and Togetherness.